Pedagogical practices for the approach to knowledge as social and natural scientists in high school students - Castelblanco, Alexandra; Cifuentes, José Eduardo; Pinilla, Diana Patricia; Pulido, Sarasbathy Debi (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents the findings of an investigation that arose from the analysis and reflection of three teachers from a public institution in the department of Cundinamarca. They observed that students, in the areas of natural and social sciences, presented low levels in the performance of argumentative, interpretative, and propositional skills; difficulty in explaining ideas and sustaining propositions and points of view; difficulty in making comparisons; and low capacity to formulate hypotheses and to provide answers in several exercises. For this reason, the research aimed to generate transformations in the classroom practices from the framework of teaching for understanding, in order to promote in students of basic secondary and high school the approach to knowledge as natural and social scientists do it. The research has a qualitative approach, with the methodology of pedagogical action research. It was possible to generate transformations in the pedagogical practices based on the constant questioning and reflection from the classroom, which led to the improvement of the students’ performance in the development of scientific competences, abilities, and attitudes.